ANALYSIS OF REGIONAL POTENTIAL AND SMALL MEDIUM INDUSTRY POTENTIAL USING LOQATION QUOTIENT (LQ), LOCALITATION INDEX (LI) AND SPECIALIZATION INDEX (SI) METHODS IN MAJALENGKA DISTRICT (Case Study: Majalengka Regency) - Detra Pandji Wiwaha; Whydiantoro Whydiantoro; Lia Milana; Budiman Budiman; Intan Kusumadewi (Jurnal Mekanika dan Manufaktur, 2022)
This research is motivated by the very rapid development of Small and MediumIndustries in Indonesia, this can make economic development in Indonesia even better. Ineconomic development in Indonesia, the role of Small and Medium Industries is quite strategic.Many parties believe that the SME sector business is able to withstand the economic crisis thathas been experienced in previous years. On the other hand, the development of the SME sectorbusiness cannot be separated from the general characteristics that most of the products producedare for the growth of domestic needs, especially in one district. Various business profiles arebriefly reviewed to provide an up- to-date overview of the small and medium industry sectorbusinesses. The type of data used in this study consists of primary data and secondary data.The primary data used is the 2018 sub-district SMI data, while the secondary data includes thename of the SMI, address, product, total production per year, the main KBLI group, KBLI,coordinate points and elevation. Data were collected using the interview method and GPStracking. The results obtained from this study are the potential distribution of Small and MediumIndustries which are spread across 26 Districts in Majalengka Regency, which in 2018 totaled1747 SMI.